Squaraine Planar-Heterojunction Solar Cells - Bin Fan; Ylenia Maniglio; Marina Simeunovic; Simon Kuster; Thomas Geiger; Roland Hany; Frank Nüesch (International Journal of Photoenergy)
The photovoltaic performance of squaraine-based organic solar cells is investigated. Two squaraine derivatives with extraordinarily high extinction coefficients are used as electron donors in bilayer heterojunctions with fullerene C60 as electron acceptor. Due to the very strong squaraine absorption band in the red spectral domain, antibatic behavior due to light filtering is observed in the photocurrent spectrum for film thicknesses of 35 nm to 40 nm. At reduced film thicknesses of 20 nm, this filtering effect at maximum absorption can be alleviated and power conversion efficiencies under simulated AM 1.5 full sun irradiation of 0.59% and 1.01% are obtained for the two squaraine derivatives, respectively. The photovoltaic properties of these cells are investigated with respect to electrode materials and chemical doping.